Characteristics of magnetic field fluctuations as observed in the magnetosheath - Tomomura, Kiyoshi; Sakurai, Tohru; Tonegawa, Yutaka (1984)
P(論文) Magnetic data obtained by the ISEE-1 and -2 satellites during twelve months from July to December, 1978 and 1979,are analyzed to clarify characteristics of low-frequency hydromagnetic fluctuations near the bow shock in the magnetosheath. Characteristics of the magnetic field fluctuations are examined by means of the spectral MEM and the minimum variance methods. The dynamic spectrum indicates that the spectral peaks appear in the frequency range from 0.01 to 0.05Hz. The spectral power of the component parallel to the average magnetic field tends to be larger than those perpendicular to the field. The angles between the wave normal vector and the average magnetic field are almost restricted within 60°-90°, i. e., the wave normal vector is directed nearly perpendicular to the magnetic field. Therefore, these characteristics strongly signify that the magnetic field fluctuations in the magnetosheath tend to be compressional mode. departmental bulletin paper